Application of fungicides in cultivation of industrial hemp to increase yield and improve product quality - I. V. Bakulova; I. I. Pluzhnikova; N. V. Kriushin (Аграрная наука Евро-Северо-Востока)
The results of research for 2022–2024 on the biological efficacy of fungicide preparations, their effect on the growth and development of plants, yield and quality of hemp products of a new cultivar of hemp ‘Ludmila’ under the conditions of Penza region are presented. The scheme of the field experiment included treatment with fungicides: soil of the experimental plot – Sterniphag, SP; seeds – Celest Top, CS; Bacsis, ZH; Bactofit, SP; Celest Top, CS+Bacsis, ZH; crops - Bacsis, ZH; Bactofit, SP. In the control variant fungicides were not applied. On average, during the years of the research, seed treatment with the studied preparations allowed increasing laboratory germination from 89.7 % in the control to 93.0–96.0 % in the protection variants, the best result was obtained with application of insectofungicide Celest Top, CS. Application of the studied preparations to hemp seeds allowed to increase the resistance of seedlings to pathogens, the biological efficiency of fungicides amounted to 40.6–77.9 %. On the plot with treatment with biological fungicide Sterniphag, SP the formation of more productive plants was noted, the increase in seed yield to the control amounted to 0.07 t/ha, or 5.6 %. The highest increase in seed yield  (0.11–0.15 t/ha) was obtained with the use of biological preparation Bacsis, ZH and insectofungicide Celest Top, CS, as well as their combination. The content of total fiber in hemp stems varied from 24.2 to 33.9 %, long fiber – from 11.3 to 20.9 %, the use of soil fungicide Sterniphag, SP increased the total fiber content by 0.93 % and long fiber by 1.52 %. Seed treatment before sowing increased the yield of long fiber by 1.04–1.92 % at 15.11 % in the control.